Micro-scale impact resistance of coatings on hardened tool steel and cemented carbide - Beake, Ben D.; Isern, Luis; Endrino, José L.; Liskiewicz, T. W.; Shi, X. (Elsevier, 2020)
Micro-impact, a novel accelerated test method for assessing coating durability under repetitive contact, has been developed to concentrate impact-induced stresses close to the interfaces in coating systems. Test results are described for carbon coatings on hardened tool steel and nitride-based coatings on cemented carbide. At higher load it was possible to show the increasing contribution of the substrate properties (load support and ductility) to the coating system response whilst retaining high sensitivity to the coating properties. Hard and elastic carbon coatings on hardened tool steel displayed very low impact resistance under these conditions. Relatively soft carbon-based coatings with more metallic character and high plasticity (low H/E) deposited on hard but tough tool steel were resistant to radial cracking and lateral fracture at high load. Lateral fracture at high load and extensive substrate cracking was observed at higher load for hard nitrides on cemented carbide. The micro-impact test has the potential to significantly speed up the pace of coating system selection for durability under highly loaded repetitive contacts, as occur in coatings applications in engine components and in discontinuous cutting operations
Keywords: Wear and tribology; Fatigue; Physical vapour deposition; Thin films